Measuring the Political Economy of Tax Lawmaking: A Methodology and Evidence from Argentina - Javier Alvaredo; Alejandro Bonvecchi; Ernesto Calvo; Maximiliano Castillo; Juan Carlos Gomez (Inter-American Development Bank (IDB), 2013)
Although recent research has shed new light on the political determinants and economic consequences of tax lawmaking, existing analyses rely on coarse data measuring political aggregates. Consequently, little is known about the political processes determining how tax legislation is written or their effect on the nature of tax reforms. This paper therefore develops a methodology to examine how Congress edits the content of tax legislation by measuring the ways Deputies, Senators, Presidents, and Ministers propose and amend such legislation. The Legislative Substance Scale proposed here measures the distance between a bills original position and the actual outcome of the legislative process by comparing the differences in content according to coding of the main tax policy dimensions. The scale is used to build the first systematic database of tax lawmaking in Argentina, and to describe its general patterns of authorship, approval and substantive content across presidencies in the current democratic period.
Keywords: D78; H20; H77; 330